2012
DOI: 10.1186/2193-9012-1-2
|View full text |Cite
|
Sign up to set email alerts
|

The future of retirement and the pension system: How the public’s expectations vary over time and across socio-economic groups

Abstract: We analyze expectations of the Dutch population ages 25 and older concerning future generosity of state and occupational pensions, the main pillars of the Dutch pension system. We use rotating panel data with monthly observations from 2006 until 2012 on individuals' subjective expectations concerning changes between now and ten or twenty years from now in the purchasing power of occupational pensions and of old age social security benefits, the eligibility age for old age social security benefits, and the aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In Europe, Bissonnette and van Soest (2011) have investigated the expectations of the Dutch population aged 25 and above concerning the future generosity of state and occupational pensions. They used monthly data for the time period May 2006 to September 2010.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In Europe, Bissonnette and van Soest (2011) have investigated the expectations of the Dutch population aged 25 and above concerning the future generosity of state and occupational pensions. They used monthly data for the time period May 2006 to September 2010.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Respondents are asked to think about "the average Dutch person", not about themselves directly. Bissonnette and van Soest (2011) found that the average reported probability that the eligibility age would increase over the next 10 years rose from about 60% in May 2006 to 70% in summer 2009 to 75% in summer 2010. Bissonnette and van Soest (2011) also investigated whether expectations were different for different socio-economic groups.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature has produced a fair amount of empirical ndings on how expectations vary across individuals and over time. Examples are studies on survival expectations ( (Hurd and McGarry, 1995)), future income ( (Dominitz, 2001)), work status ( (Stephens Jr, 2004)), ination ((Bruine de Bruin and Manski, 2011)), pensions and retirement ages ( (Bissonnette and Van Soest, 2012)), retirement income replacement rates ((De Bresser and van Soest, 2013b)), and returns on nancial assets ((Dominitz and Manski, 2007)). See also Manski (2004) and Hurd (2009) for excellent overviews.…”
Section: Introductionmentioning
confidence: 99%